Earth-making. Institution and expression in Maurice Merleau-Ponty (Itinera, 2023)
In this article, we aim to focus on the notion of Earth in Merleau-Ponty’s reflections on the concept of nature and his reinterpretation of the Husserlian Umsturz. In doing so, we will use the expression “Earth-making” to describe a particular instituting dynamic, where by the term “institution” we wish to refer to the Husserlian concept of Stiftung and its original reworking by Merleau-Ponty during his 1954-55 course at the Collège de France: L’institution - La Passivité.We will therefore identify the concept of institution as a privileged way to describe our relationship with the Earth, understood as Boden [soil], envisaging in the instituting dynamic as something close to art. Finally, we will try to illustrate what Merleau-Ponty means by transcendental geology, namely the capacity to grasp the original relationship between space and time and a new way of conceptualizing the Earth as a